(untitled) (Asian Journal of Medical and Biological Research, 2025)
Osteoporosis is a silent, progressive skeletal disorder characterized by decreased bone strength, leading to an increased risk of fractures, particularly among aging populations. This cross-sectional study was conducted over six months from June to December 2018 in the Tatibazar area of Old Dhaka, Bangladesh, to assess bone health using quantitative ultrasound (QUS) and estimate fracture risk through the Fracture Risk Assessment Tool (FRAX). A total of 188 conveniently selected participants aged 40 years and older underwent BMD screening with QUS. The FRAX tool, a validated clinical prediction model, was used to calculate the 10-year probability of major osteoporotic fractures (MOF) and hip fractures (HF) based on clinical risk factors, with and without BMD input. The prevalence of osteopenia and osteoporosis was 31.4% and 11.2%, respectively. Age group (P < 0.001), BMI (P = 0.013), and smoking (P = 0.019) were significantly associated with lower T-scores. According to FRAX with BMD, 5.3% of participants had a moderate to high risk of MOF, and 12.2% had a high risk of HF. Age, prior fracture, glucocorticoid use, and rheumatoid arthritis were significantly linked to MOF risk; age, BMI, smoking, glucocorticoid use, and rheumatoid arthritis were linked to HF risk. The findings highlight a high burden of reduced bone mass and fracture risk in the urban aging population of Dhaka. These results emphasize the need for early diagnosis and preventive strategies, especially in resource-limited settings. Further studies are required to validate the effectiveness of QUS and FRAX as population-level screening tools in Bangladesh. Asian J. Med. Biol. Res. 2025, 11(3), 49-58